Propuesta de un Circuito Turístico de deportes Extremos en el sector Puerto Bajaña del Cantón Buena Fe, Año 2019 - Camacho Ramírez, Jhon Alexander (2019)
The following research is aimed at the proposal of a touristic circuit of extreme sports in the sector Bajaña port, Ecuador 2019, owned by Mr. Joel Vizcarra, located in the Bajaña port sector. The reason for the project is to learn about adventure tourism. The fieldwork was carried out, identified by area analysis and taking coordinates for the design of the extreme sports tourist circuit. 388 surveys were carried out in order to know the acceptance of the demand for the creation of a tourist circuit, with a service of rental of vehicles for the practice of extreme sports in the sector. With 97.2%, the cost to pay for making use of the circuit will be worth US$ 25.00 per person each sport will have a different value. Keywords: Proposal, extreme sports, modalities, adventure tourism.